Profile of dehydration fever in a medical college hospital sick newborn care unit - Bag, Toshibananda; Karan, Subhajit; Saha, Mousumi (Indian Journal of Child Health, 2019)
Background: Neonatal fever due to dehydration is common in warm climatic conditions. There are reports of serious complications of dehydration fever such as seizures, disseminated intravenous coagulation, acute kidney injury, multiple cerebrovascular accidents, and even fatalities. Objectives: The objectives of the study were to determine the number of newborns admitted into the sick newborn care unit (SNCU) with dehydration fever, to ascertain about other associated comorbid conditions, and to know the outcome of these newborns following treatment. Materials and Methods: Data were collected from the SNCU records of neonates admitted with fever with no evidence of infection during three summer months (April, May, and June) in the years 2018 and 2019. Status of hydration in all such babies at the time of admission was noted (as clinically evident by loss of more than 10% of birth weight, decreased urination, dryness of the oral cavity and eyes, loss of skin turgor, and sunken anterior fontanelle). The outcome of all the neonates, who were treated according to the existing protocol, were also noted. Results: Out of the total 4570 neonates admitted during the study period, 52 (1.094%) were having dehydration fever. Among them, 8 (15.38%) were preterm, 11 (21.15%) were intrauterine growth restriction, and the rest 33 (63.46%) were term, appropriate for gestation. Males were slightly more than females (29:23). Electrolyte imbalance was not seen in any of the babies. Although, initially, all the babies were lethargic, they all improved promptly following intravenous rehydration along with the maintenance of thermoneutral environment and the maximum hospital stay noted was only 3 days. Conclusion: Fever in newborn due to pure dehydration, even without electrolyte imbalance exists, and it should be considered in warm climatic condition.